Effectiveness of Educational Program on Nurse's Knowledge and Practices Regarding Management of Pregnancy with Danger Signs - Asala Riyadh Mohammed, Hawraa Hussein Ghafel, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Proper knowledge about danger signs, emergency measures to be taken, and a well-equipped obstetrics unit can reduce maternal mortality. As the nurses being the primary health care providers, their preparedness for obstetrics emergencies attains paramount importance. Objective: the study aimed to determine impact of educational program on nurses’ knowledge and practice about management of pregnancy with danger signs and to find out relationship between educational program efficacy and these nurses’ specific demographic characteristics Methodology: To identify the effectiveness of the educational program on nurses' knowledge and practice, a quasi-experimental study design was used. A non-probability (purposive sample) consist of (50) nurses who used the words "emergency," "labor room," and "maternal wards." The questionnaire is consist of three main parts: demographic information about the nurses, as well as knowledge and practice in managing danger signs in pregnant women. Results: The study shows that the overall assessment of nurses’ knowledge about management of pregnancy with danger signs; the findings reveal that nurses are showing fair level of knowledge during the pre-test time (36.56±2.771) among 84%, their level of knowledge is increased to good level during the post-test 1 (90%) and post-test 2 (82%) evidenced by mean scores and standard deviation (post 1= 45.98±2.470, post 2= 45.20±3.188) and the overall assessment of nurses’ practices about management of pregnancy with danger signs; the findings reveal that nurses are showing fair level of practices during the pre-test time (78.14±5.047) among 96%, and they show improvement in their practices’ level as show good during the post-test 1 (78%) and post-test 2 (76%) evidenced by mean scores and standard deviation (post 1= 104.86± 10.791, post 2= 104.10 ± 10.873) Conclusions: the educational program about management of pregnancy with danger signs was highly effective on nurses' knowledge and practice. So, the study recommends the need to prepare and present continuous educational programs to improve the knowledge and practices of nurses and midwives.